2015
DOI: 10.1039/c4cp06103a
|View full text |Cite
|
Sign up to set email alerts
|

A study of optical absorption of cysteine-capped CdSe nanoclusters using first-principles calculations

Abstract: Understanding the size-dependent structures and properties of ligand-capped nanoclusters in solvent is of particular interest for the design, synthesis and application of II-VI colloidal QDs. Using DFT and TDDFT calculations, we studied the structure and optical property evolution of the cysteine-capped (CdSe)N clusters of N = 1-10, 13, 16 and 19 in gas, toluene, water and alkaline aqueous solution, and made a comparison with their corresponding bare clusters. The cysteine binds with (CdSe)Nvia several pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…Such computational methodology has been extensively tested and used across a broad variety of previous modeling studies. 31,35,36,47,69,70 Hirshfeld 61 charge analysis, as applied in Multiwfn 71 v3.7 software package, was used to obtain the charge distribution on all the atoms and calculate the Inverse Participation Ratios (IPRs). We obtained the partial density of states (PDOS) plots from Gaussian outputs using GaussSum software package 72 and visualized atomic structures and orbitals using the VESTA 73 v3.5.7 software.…”
Section: Methodsmentioning
confidence: 99%
“…Such computational methodology has been extensively tested and used across a broad variety of previous modeling studies. 31,35,36,47,69,70 Hirshfeld 61 charge analysis, as applied in Multiwfn 71 v3.7 software package, was used to obtain the charge distribution on all the atoms and calculate the Inverse Participation Ratios (IPRs). We obtained the partial density of states (PDOS) plots from Gaussian outputs using GaussSum software package 72 and visualized atomic structures and orbitals using the VESTA 73 v3.5.7 software.…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations 59 revealed that the interaction patterns between Cys and (CdSe) n vary with the cluster size and medium. Pattern S → Cd ← N is preferred in the gas phase, toluene, and alkaline solution, while pattern O → Cd and H → Se is preferred in water.…”
Section: Some Investigations Of Cys Binding Modes On the Surface Ofmentioning
confidence: 99%
“…43 First-principles calculation on cysteine-coordinated (CdSe) N nanoclusters ( N = 1–10, 13, 16, and 19) shows that the sulfur and oxygen atoms of cysteine in alkaline solution cannot simultaneously coordinate to a cadmium atom at the surface of CdSe nanoclusters because of the structural rigidity of cysteine. 44 Hence, in cysteine-capped (CdSe) 34 , it is also unlikely for the carboxylate group to form bridging coordination to sodium and cadmium. To conclude, the carboxylate group of ligand–cysteine binds to the counter Na + ions in the solid-state CdSe-Cys and not to the CdSe core surface.…”
Section: Resultsmentioning
confidence: 99%